Interactive multimedia library products: forming skills of technology while preparing bachelors of library and information activities - S. V. Savkina (Библиосфера, 2018)
Currently, the range of information products and services provided remotely is developing and expanding. Modern library users often prefer remote services to traditional forms. The real communication is inferior to virtual one, the popularity of electronic information products is growing. Libraries transform popular traditional products and services into electronic formats. So traditional quizzes, which are popular in libraries, are moving into a new form, become a dynamically developing electronic product. The popularity and demand of multimedia products for modern users led to emerging a wide range of such products in the library practice. Multimedia capabilities combine different forms of information and provide visibility, visual appeal and increase interest among users. The most original of them are the products with interactive features that provide the opportunity to dialogue with users and implement active actions. The most popular are such interactive multimedia products as an electronic interactive exhibition, a multimedia interactive quiz, a video with interactive elements. Libraries can also develop such products without extensive software, hardware and human resources. To ensure the quality of the created interactive multimedia products, it is necessary to study the technology of their preparation. Based on the interactive multimedia works created by students the author considers their features, cases of interactive opportunities realization; characterizes the experience to form of skills of technology of their preparation at bachelors of library and information activity. Actively developing of remote library services using information-communicating technologies, transforming traditional forms into multimedia format contributes to the development of interactive multimedia forms, as well as allows attracting users and increase the demand for documents. Game forms of work with readers are especially relevant for children and youth audience. Development and implementtation of multimedia interactive product is economically less labor-intensive process than the traditional library event.